2011
DOI: 10.1155/2011/312492
|View full text |Cite
|
Sign up to set email alerts
|

Health and Functional Status of Adults with Intellectual Disability Referred to the Specialist Health Care Setting: A Five-Year Experience

Abstract: Aims and Method. The Developmental Disability Database in the Department of Rehabilitation Medicine at a metropolitan hospital was audited for observations on adults with Intellectual Disability living in the local region (total population 180,000) who were seen in an identified multidisciplinary specialist clinic, during 2006–2010. Results. There were 162 people (representing half the known number of adults with Intellectual Disability living in the region): 77 females, 85 males, age range 16–86 years. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
(18 reference statements)
3
5
0
Order By: Relevance
“…We observed that PEG‐J was required in five patients (12%), although unfortunately it is difficult to predict, even retrospectively, which patients may have benefitted from this at the outset, as functional GI symptoms are relatively common in learning disabilities patients (Lee et al . ). Decisions relating to whether the procedure was performed under GA (in preference to conscious sedation) were made pre‐emptively where possible if prior endoscopy had been technically difficult or where there was concern regarding compliance or respiratory reserve.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We observed that PEG‐J was required in five patients (12%), although unfortunately it is difficult to predict, even retrospectively, which patients may have benefitted from this at the outset, as functional GI symptoms are relatively common in learning disabilities patients (Lee et al . ). Decisions relating to whether the procedure was performed under GA (in preference to conscious sedation) were made pre‐emptively where possible if prior endoscopy had been technically difficult or where there was concern regarding compliance or respiratory reserve.…”
Section: Discussionmentioning
confidence: 97%
“…Functional gastrointestinal problems are also relatively frequent in the context of learning disabilities and include gastro‐oesophageal reflux disease which may affect up to 36% (Lee et al . ), constipation and vomiting.…”
Section: Introductionmentioning
confidence: 99%
“…Duplicates removed (n = 868) 4 articles reported on same study 2 articles reported on same study 108,115,116,132,138,141 ) and South Africa (n = 2 131,134 ). Primarily, the included studies were cross-sectional observational (n = 31 81,82,98,[100][101][102]104,106,[109][110][111]114,116,119,121,124,[126][127][128][129][130][131][132][133][134][135]137,139,142,143,145 ).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Primarily, the included studies were cross-sectional observational (n = 31 81,82,98,[100][101][102]104,106,[109][110][111]114,116,119,121,124,[126][127][128][129][130][131][132][133][134][135]137,139,142,143,145 ). The remaining studies involved retrospective database or medical records data (n = 22 [83][84][85][86][87][88][89]94,95,99,107,113,115,117,118,120,122,123,136,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Because of a higher prevalence of health conditions and preexisting conditions, people with intellectual disability also tend to be on multiple medications (Lee et al, 2011). Recently, a systematic review and a meta-analysis study had a consistent conclusion that the medications associated with an increased risk of falling were benzodiazepines (hypnosedatives), antidepressants, and antipsychotics; a weak association was found between anticonvulsants, antihypertensives, and an increased risk of falling (Hartikainen et al, 2007;Woolcott et al, 2009).…”
Section: Medical Factorsmentioning
confidence: 99%